AutoBank E: e-banking for rural South Africans - Mali, Lincoln (Technical Centre for Agricultural and Rural Cooperation, 2003)
Lincoln Mali explains how a local bank in South Africa is extending its network of ATMs in rural areas. The initiative is bringing basic banking services within the reach of farmers.